Profil Kadar Hemoglobin dan Indeks Eritrosit pada Perokok Aktif di Kelurahan Tanjung Pinang Kota Palangka Raya - Rinny Ardina; Vira Anisa Monica (Jurnal Surya Medika (JSM), 2018)
Active smokers are people who are smoking continuously. The population of active smokers in Central Kalimantan was 26,5% in 2013. Cigarettes contain many toxic and addictive chemicals. The presence of tar and free radicals from cigarette smoke can cause erythrocyte hemolysis. In addition, the content of cigarette smoke can also cause an increase in hemoglobin levels that mediated by exposure to Carbon monoxide (CO). CO binds avidly to hemoglobin to form carboxyhemoglobin (HbCO). This study aims to give a description of hemoglobin level and erythrocyte indices in active smokers in Kelurahan Tanjung Pinang, Palangka Raya. The descriptive observational method with the cross-sectional design was used in this study. The sample obtained by 28 people with purposive sampling technique with criteria such as active smokers, men, working as farmers, laborers or fish farmers and not alcoholic. Examination of hemoglobin level and erythrocytes indices was done by a hematology analyzer. The result showed that 4 people (14,2%) had low hemoglobin level and 4 people (85,7%) was normal. Based on erythrocytes indices, 2 people (7,1%) with hypochromic microcytic anemia (low MCV, low MCH, and normal MCHC) and also low hemoglobin level. While 26 people (92,8%) had normal erythrocyte indices.